2018
DOI: 10.1002/sscp.201800084
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of chitosan‐siloxane magnetic nanoparticles for the extraction of pesticides from water and determination by HPLC

Abstract: Novel chitosan‐siloxane functionalized magnetic nanoparticles including chitosan polydimethyl siloxane, chitosan octadecyl siloxane, and chitosan phenyl siloxane were prepared and characterized by Fourier transform infrared spectroscopy, scanning electron microscopy and Zeta potential measurements. The particles were prepared from Fe3O4 functionalized by siloxane derivatives followed by coating with chitosan through a crosslinking mechanism. Infrared spectroscopy was used to confirm the reaction and conjugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The characteristics of developed method and the comparison of the amount of adsorbent, the type and amount of extraction solvent, extraction time, RSD (%) and LOD were listed in Table 5. It can be seen that the LODs of this method were lower than those achieved by SPE (Esteve-Turrillas et al, 2005), LLE-DLLME (Farajzadeh et al, 2014), and MDSPE (Badawy et al, 2018). In comparison with other methods, the amounts of adsorbent and extraction solvent were obviously reduced: only 1.5 μg/mL of DES-G and 100 μL of acetonitrile.…”
Section: Results and Conclusionmentioning
confidence: 77%
“…The characteristics of developed method and the comparison of the amount of adsorbent, the type and amount of extraction solvent, extraction time, RSD (%) and LOD were listed in Table 5. It can be seen that the LODs of this method were lower than those achieved by SPE (Esteve-Turrillas et al, 2005), LLE-DLLME (Farajzadeh et al, 2014), and MDSPE (Badawy et al, 2018). In comparison with other methods, the amounts of adsorbent and extraction solvent were obviously reduced: only 1.5 μg/mL of DES-G and 100 μL of acetonitrile.…”
Section: Results and Conclusionmentioning
confidence: 77%
“…Therefore, we completed this reaction in our study by crosslinking agent to cover the reactive functional groups (amino and hydroxyl). Recently, we prepared chitosan‐siloxane magnetic nanoparticles from Fe 3 O 4 functionalized by siloxane derivatives followed by coating with chitosan through a crosslinking mechanism using glutaraldehyde and epichlorohydrin [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The SPE cartridge was performed using a plastic syringe column of 0.9 cm diameter and 9 cm in length ( Figure 1 ). The column was filled up without gaps by compressing a frit on the bottom and then adding 0.25 g of each Ch-MO NPs and stopcock frit on the upper [ 34 ]. We compared these cartridges with the ODS (C18, Supelco) cartridge as it is the most common material used in extraction and clean-up of pesticide residues.…”
Section: Methodsmentioning
confidence: 99%
“…177 These techniques were applied for the removal of diazinon, abamectin, fenamiphos, imidaclopride, methomyl and thiophanate methyl from water using new chitosan siloxane functionalized magnetic nanoparticles (Ch-SiMNPs). 178 The capture of all pesticides was experimented in three stages using 50, 100 and 200 μg/ml dispersed in water and was found that increasing the content of Ch-Si MNPs, the pesticide percentage recovery also increased. Abamectin indicated greatest recovery among all the pesticides and imidacloprid showed the least.…”
Section: Magnetic Chitosan Adsorbent For Other Organic Compoundsmentioning
confidence: 99%